The role of minimal residual disease elimination in the outcome of chronic lymphocytic leukemia (Hematology Meeting Reports, 2009)
There have been significant changes during the past few decades in the management of chronic lymphocytic leukemia (CLL), a disease with a very heterogeneous outcome ranging from survival for decades, without evidence of progression, to rapid transformation into more aggressive disease and early death.1 An increasing awareness of the prognostic factors and molecular heterogeneity of CLL has helped to identify distinct risk categories, enabling early identification of patients likely to develop more aggressive disease. In addition, newer treatment agents and strategies, including monoclonal antibodies and hematopoietic stem cell transplantation (SCT), have resulted in much higher complete response (CR) rates than seen previously with conventional therapy.